"Confucian management" or a confused and epistemologically questionable view on Chinese management?. Issue 3 (9th October 2017) - Friend, Anthony
Abstract : Purpose: In the wake of the ongoing financial crisis, US managerialism has been denounced as a professional caste that has slowly served to erode the competitiveness of the US economy. In light of this, there is an increasing search for possible alternatives to US managerialism, with some authorities putting forward that one enviable alternative is "Confucian management", which they claim is a means of organising in Chinese institutions that gets things done by pulling on the rich heritage of Ancient Chinese philosophy. The purpose of this paper is to interrogate "Confucian management". Design/methodology/approach: This paper questions the common view of "Confucian management" through an ethnography of Baiyun University (a pseudonym) in South China, where the author worked as a "foreign" English lecturer for one academic year, and in order to do this the author draws on participant-observation and semi-structured interviews. Ethnography has long been associated with colonialism and has more recently been connected with post-colonialism, so in an attempt to decolonise the methodology, the author analyses the generated research data through a Chinese sensitive cultural framework. Findings: This paper argues that "Confucian management" offers a confused and epistemologically questionable view on Chinese management. It points to some of the limitations of management and organisation studies brought about by claims being made without sufficient empirical evidence. Research limitations/implications: The focus is on "Confucian management" at Baiyun University so findings are specific to this empirical research site. It is also acknowledged that universities have a divergent form of management to other institutions. The paper's intent is ideographic rather than nomothetic; therefore, no claims to generalisation are made. Originality/value: The paper makes three substantive contributions. First, the empirical contribution is an ethnographic description of "Confucian management" at Baiyun University. Second, the methodological contribution attempts to decolonise methodology by analysing the generated research data through a Chinese sensitive cultural framework. Third, the epistemological contribution queries to what extent "Confucian management" as an idea that is enunciated from the Global North is able to effectively speak about a practice that is supposedly performed in the Global South.